Assessing the Inter-observer Agreement of Electrocardiography Interpretation in the Elderly Surgical Patients: A Cross-Sectional Study - Mupangati, Yudo Murti; Setyawan, Henry; Soejono, Czeresna Heriawan; Gasem, Muhammad Hussein; Riwanto, Ignatius (RSUP Dr. Kariadi, 2023)
Background: Electrocardiography (ECG) is an essential objective diagnosis tool, specifically for the elderly who are about to undergo surgery. From the examination results, it is possible to determine the presence of a heart condition that could impair the surgical outcome. Furthermore, the examination is slightly influenced by the subjectivity of observers. Purpose: To evaluate the inter-observer agreement on the reader of a 12-lead ECG on elderly patients subjected to elective surgery. Method: A consequential ECG examination was conducted on elderly patients who underwent elective surgery at Dr. Kariadi Hospital Semarang between July and November 2021. Two junior internist observers were independently involved in reading the ECG results in different places. The inter-observer reliability analysis used kappa statistics to determine consistency between observers. Result: Analysis was carried out on 193 patients aged 60-87 years old, with a prevalence of abnormal ECG was 33.7%. Kappa Conformity Value was 0.864 (95 % CI: 0.790-0.938, p<0.001). Conclusion: The value of agreement between junior internists in ECG interpretation among elderly surgical patients is good (kappa value >0.8). Even though the observers are junior internist, the result of the interpretation with a high kappa is considered to have reliable validity.